Antibiotic Use Evaluation in ICU/HCU of Muhammadiyah University General Hospital Malang using DDD and Gyssens Methods - Hidajah Rachmawati; Muktamiroh Muktamiroh; Didik Hasmono; Atika Putri Kusumaningtyas; Sendi Lia Yunita; Lilik Yusetyani (Fakultas Kedokteran Universitas Brawijaya, 2023)
Infection is a condition caused by the propagation of harmful microorganisms with or without clinical symptoms. Improper use of antibiotics can lead to antibiotic resistance. The Ministry of Health of the Republic of Indonesia recommended a quantitative evaluation of the use of antibiotics using the Defined Daily Dose (DDD) method and a qualitative evaluation using the Gyssens method. This study evaluated antibiotics usage using DDD and Gyssens methods in ICU/HCU of the Muhammadiyah University General Hospital Malang. Employing retrospective observational method, data were collected from patient medical records hospitalized during January-December 2020. Results of the DDD quantitative analysis showed that the most widely used antibiotic was Ceftriaxone with a 35.79 DDD/100 patient-days. The Gyssenss qualitative analysis showed that the category VI (incomplete patient's medical record data) was 3%, category IVa (antibiotic use is more effective) (2%), category IIIb (duration of antibiotic use is too short) (3%), category IIb (antibiotic use is not at the right interval) (3%).